The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1128/jb.133.2.987-994.1978
|View full text |Cite
|
Sign up to set email alerts
|

Caulobacter crescentus cell envelope: effect of growth conditions on murein and outer membrane protein composition

Abstract: The murein and membrane protein compositions of Caulobacter crescentus strains CB13B1a and CB15 have been characterized, and the influence on cell envelope constituents of culture conditions which affect morphogenesis have been studied. Amino acid and amino sugar analysis of murein sacculi revealed a simple AlY murein configuration typical of gram-negative bacteria. The membranes of C. crescentus had low levels of 2-keto-3-deoxyoctonate relative to enteric bacteria, in addition to the absence of lipid A compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Results of NADH dehydrogenase assays on the membrane fraction with potassium ferricyanide as the electron acceptor showed that indeed fraction III exhibited a very high NADH dehydrogenase activity. Succinate dehydrogenase activity has also been used as a marker of the cytoplasmic membrane (1,5,11,17,18,22,23,35,44). As shown in Table 2, this activity appeared to be significantly enriched in fraction I.…”
Section: Isolation Of the Membrane Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of NADH dehydrogenase assays on the membrane fraction with potassium ferricyanide as the electron acceptor showed that indeed fraction III exhibited a very high NADH dehydrogenase activity. Succinate dehydrogenase activity has also been used as a marker of the cytoplasmic membrane (1,5,11,17,18,22,23,35,44). As shown in Table 2, this activity appeared to be significantly enriched in fraction I.…”
Section: Isolation Of the Membrane Fractionsmentioning
confidence: 99%
“…Fraction II, which proved to be unresolved cytoplasmic and outer membrane, contained approximately 15% of the total recovered membrane protein. KDO, an eight-carbon sugar specific to LPS, has been used in numerous studies as the definitive marker of the outer membrane (1,5,22,23,35,39,40,44). KDO was present in M. xanthus in concentrations of approximately 5 x 10-12 ,mol/cell.…”
Section: Isolation Of the Membrane Fractionsmentioning
confidence: 99%
“…Although the outer membrane of Escherichia coli has been well studied and maniy observations about it are applicable to the membranes of other organisms, it is becoming clear that the outer membranes of free-living organisms may be more complex than the outer membranes of enterics. For example, the Caulobacter crescentus outer membrane has a major membrane protein but also has a preponderance of high-molecular-weight polypeptides (1). The Pseudomonas aeruginosa outer membrane also has a greater variety of proteins, but only a few minor proteins are above a molecular weight of 50,000 (12,14).…”
mentioning
confidence: 99%
“…We have not been able to reliably separate the proteins of the inner and outer membranes of Caulobacter by standard methods involving sucrose density gradient centrifugation or differential detergent solubility of membranes (Hancock and Nikaido, unpublished data; Walker and Smit, unpublished data). Despite reports by others of successful segregation of Caulobacter membranes [26,27], in our experience the methods yield membrane fractions with nearly identical protein profiles. Surface labeling with porin P antibody gave negative results, yet 221 was not definitive, since the antibodies used in this study are unable to label P. aeruginosa cells grown under phosphate limitation with rough or smooth LPS.…”
Section: Resultsmentioning
confidence: 64%